Oculo-auriculo-vertebral spectrum with complete absence of the right condyle and ramus - Case report - Ali Hassani; Hamidreza Mahaseni Aghdam; Sahar Fazel; Farnaz Keyhanlou (Elsevier, 2019)
Oculo-auriculo-vertebral spectrum (OAVS), formerly known as Goldenhar syndrome is a complex congenital anomaly arising from mal-development of first and second branchial arches, mainly affecting the face, eyes and ears. Majority of patients diagnosed with OAVS have some degree of facial asymmetry, featured with unilateral facial hypoplasia, prominent forehead, hypoplasia of the zygomatic area, maxilla and mandible. Herewith, we report a case of OAVS in a 13-year-old male who presented with Kaban type III TMJ deformity, in addition to facial and skeletal dysmorphology. Keywords: Oculo-auriculo-vertebral spectrum, Goldenhar syndrome, Hemifacial microsomia